The role of SPIRE proteins in melanosome dispersion in skin melanocytes - Alzahofi, Noura (2020)
A critical physiological process for living cells is to transport their organelles and other material from their site of formation to their site of function. This transport process involves complex cooperation between many different proteins that function as signals, docking factors, motors and tracks. However, the molecular mechanisms that regulate intracellular motility remain mostly obscure. In this study, melanosome of skin melanocytes was used as a model for lysosome-related organelles, and in particular to study the role of SPIRE1/2 (the actin nucleator factors) in intracellular trafficking. More specifically, the role of conserved SPIRE1/2 domains has been investigated in melanosome transport in two ways. Firstly, SPIRE1/2 rescue assay was conducted, in which the translation of endogenous SPIRE1/2-mRNA was disrupted by specific short-interference RNA, and then the cells were rescued by adding siRNA-resistant SPIRE1/2 (full-length, truncations, or mutations). The changes in melanosome distributions were used as a read-out for the effects of SPIRE1/2 on the transport. Secondly, a modified nano-scale pulldown assay was performed in leaden melanocytes (melan-ln; melanophilin null melanocytes). In this approach, the active motor and lever arm of myosin-Va was attached to SPIRE1/2 (full-length, truncations, or mutations) and then expressed in melan-ln. The changes in melanosome distribution were used as a read-out for the interaction between the SPIRE construct and active Rab27a on the melanosome membrane. The results of siRNA knockdown and rescue assays provided evidence for a crucial role of SPIRE-nucleated actin in melanosome transport. The interactions with both G-actin and FMN-type formin were found to be essential for this process. The modified nano-scale pulldown assay, along with co-immunoprecipitation, provided consistent evidence of the interaction between SPIRE1 and GTP-Rab27a as well as support considering SPIRE1 as a potential Rab27a effector. The results of the knockdown-rescue assay also revealed the role of SPIRE localisation on melanosome dispersion pattern. SPIRE localising to melanosome membrane via interacting with GTP-Rab27a resulted in a uniformly dispersed distribution, while mislocalised SPIRE that did not interact with Rab27a resulted in an eccentrically dispersed distribution (hyper-dispersed). These results highlight the molecular mechanism of actin-based melanosome transport. However, further investigation is needed to determine the similarities and differences between SPIRE1 and other Rab27a effectors. Additionally, the hyper-dispersed distribution is worth investigating in depth.